1985
DOI: 10.1111/j.1550-7408.1985.tb03033.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases of the Cytolytic Mechanisms of Entamoeba histolytica1

Abstract: The cellular bases of the powerful cytolytic activity of the human protozoan parasite Entamoeba histolytica were explored by studying the effect of the virulent strain HM1:IMSS on epithelial monolayers of MDCK cells using a combination of time-lapse microcinematography and transmission and scanning electron microscopy. Early alterations of the epithelial cell membranes were detected by measuring changes in the transepithelial electrical resistance of MDCK monolayers mounted in Ussing chambers. The aggressive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
(9 reference statements)
5
54
1
Order By: Relevance
“…Cross & Matthews (1993) reported that carp leukocytes which come into close contact with Ichthyophthirius multifiliis trophozoites are generally degraded, presumably due to lytic enzymes and/or metabolites released by the parasite. Cell infiltration around invading Entamoeba histolytica also leads to rapid lysis of inflammatory cells followed by tissue necrosis (Martínez-Palomo et al 1985, Shibayama et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Cross & Matthews (1993) reported that carp leukocytes which come into close contact with Ichthyophthirius multifiliis trophozoites are generally degraded, presumably due to lytic enzymes and/or metabolites released by the parasite. Cell infiltration around invading Entamoeba histolytica also leads to rapid lysis of inflammatory cells followed by tissue necrosis (Martínez-Palomo et al 1985, Shibayama et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…3). In vitro, time-lapse microcinematography has shown that the aggressive mechanism of E. histolytica is a complex multifactorial phenomenon that includes adhesion, a contact-dependent "hit-and-run" damage to the plasma membrane of effector cells, phagocytosis, and intracellular degradation of ingested cells (86). The adhesion and cytolytic events have been related to three types of molecules: lectins, amebapores, and proteases.…”
Section: Early Invasive Lesions With Superficial Ulcerationmentioning
confidence: 99%
“…Tight junction complexes are linked to the actin cytoskeleton (60). Selective disturbance of tight junction complexes by trophozoites from E. histolytica results in the rapid decrease of the transepithelial electrical resistance caused by an increase in paracellular permeability (51,54,61).…”
Section: Parasite-enterocyte Interactionmentioning
confidence: 99%